Ground Improvement and Monitoring for a Reclamation on Reclaimed Soft Soil in Singapore - Patrick Mengé; Thomas Vergote; Johny Van Acker; Handojo Ronald Yohanson (Indonesian Geotechnical Journal, 2023)
Land reclamation works for land development and harbor construction generally require large amounts of sand. At the same time the dredging of access channels, berth pockets and turning circles for shipping may generate both, ‘suitable’ and ‘unsuitable’ dredged sediments. The definition of suitable in general focusses on well compactable granular material with a low fines content. However, in the present times of environmental awareness and search for sustainable solutions, the offshore dumping and disposing of ‘unsuitable’ fine-grained material is not deemed sustainable anymore. In this paper the Tuas Terminal Phase 1 (TTP1) in Singapore will be discussed. All dredged soft clay and residual soils were used in the reclamation and capped with a layer of limited thickness of clean sand. To achieve the design requirements, ground improvement by means of surcharge with prefabricated vertical drains (PVD’s) was performed. To demonstrate the effectiveness and results of the ground improvement works, extensive monitoring by means of settlement beacons and clusters of extensometers and porewater pressure meters was setup. Even on-site developed ‘floating’ piezometers were developed to monitor the consolidating slurry. The execution of these works required adapted execution and advanced design methods. The design and prediction of the behavior of the sediments during improvement and on the long term was a challenge. The correct prediction of deformations and the level of the soft soil-granular soil interface was important to guarantee the correct sand cap thickness after ground improvement. The long-term behavior after overconsolidation through ground improvement was studied in detail. This has led to the development of a more correct prediction method to estimate the secondary settlements of PVD-improved overconsolidated soft soil. The reclamation of the TTP1 terminal proved to be a success where stringent design requirements were met while re-using ‘unsuitable’ material and minimizing the import of clean sand.